Opening the pandora box of issues in the industrialized building system in Malaysia: a thematic review - Mohd Noor, Mohd Zairul (The Mattingley Publishing, 2020)
Under the Malaysian construction industry transformation programme (CITP) 2016-2020, IBS has been proposed as one of the alternative solutions to replace conventional construction. A lot of IBS advantages have been documented and discovered since its first implementation in the ‟90s. However, there is a lack of review paper that deliberates on IBS issues in the literature. Hence, this paper adopts a thematic review based on the issues captured in the IBS publications from 2012 till 2019. The strategy of the article was investigated via an extensive review paper on IBS and analysed using thematic analysis by ATLAS.ti 8 software. The findings from the code-to-document report in ATLAS.ti 8 found that the pattern and trends on IBS highlighted several issues in the literature. The outcomes benefit the future research direction and identify the gap for future solutions in the IBS related projects in Malaysia.